The Development of Moesaik Edutainment (Education and Entertainment) for Taxation Topic for Senior High School - Fadhilah, Siti Nur Hidayatun; Inayati, Ro’ufah (Classroom Action Research Journal (CARJO), 2020)
The purpose of this study is to produce an Economic Module Based on Edutainment on Taxation Material. In addition, to test the feasibility and attractiveness of the developed economic modules. This research is a development study using ADDIE development model which consists of five stages, namely Analyze, Design, Development, Implementation, and Evaluation. The feasibility of the product in the form of Edutainment-Based Economic Modules according to experts obtained a percentage of 90.45% with the equivalent of "Very Eligible or Valid" for use in learning.